Aktivitas Penghambatan Radikal Bebas Difenil Pikril Hidrazil (DPPH) Ekstrak Daun Macaranga magna Turrill: DPPH Free Radical Scavenger Activity of Macaranga magna Turrill Leaves Extract - Minarti Minarti; Novita Ariani; Teni Ernawati; Akhmad Darmawan (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Degenerative disease is a disease that has a large number of sufferers in Indonesia and throughout the world, one of the causes of many sufferers of degenerative diseases such as diabetes and cancer is the large amount of exposure to free radicals in the body as a result of an unhealthy lifestyle. Antioxidant compounds are one of the chemical compounds that can be used and utilized to inhibit the oxidation process as a result of the presence of free radicals, so that the incidence of degenerative diseases can be suppressed. In this study, the active extraction and fractionation process from Macaranga magna Turrill leaves which have antioxidant activity and can be developed as a compound inhibiting the oxidation process of free radicals using the chromatographic method, as well as testing the antioxidant activity using the free radical inhibition method 1,1-diphenyl-2- picrylhydrazyl (DPPH). Preliminary test results of antioxidant activity on the methanol extract of Macaranga magna Turrill leaves are known that this plant has potential as an antioxidant with an IC50 value of 11.13 ?g/mL, this is also supported by the test results of total flavonoids 19.47 mg QE/g extract and total phenol 37, 77 mg GAE/g extract.